GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 12830 species occurrences available in GBIF matching the query: TaxonKey: Lagomorpha Geometry: POLYGON((-139.35 2.59,-139.35 35.21,-84.24 35.21,-84.24 2.59,-139.35 2.59)) HasGeospatialIssue: false. The dataset includes 12830 records from 85 constituent datasets: 119 records from International Barcode of Life project (iBOL). 592 records from MVZ Mammal Collection (Arctos). 987 records from KUBI Mammalogy Collection. 29 records from MLZ Mammal Collection (Arctos). 84 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 3 records from University of Florida Vertebrate Paleontology. 3 records from CUMV Mammal Collection (Arctos). 4 records from UAM Mammal Collection (Arctos). 1 records from Cowan Tetrapod Collection - Mammals. 196 records from Field Museum of Natural History (Zoology) Mammal Collection. 38 records from CHAS Mammalogy Collection (Arctos). 18 records from Museum of Comparative Zoology, Harvard University. 5 records from NMMNH Mammal. 1372 records from iNaturalist Research-grade Observations. 12 records from Mammals housed at MHNG, Geneva. 19 records from DMNS Mammal Collection (Arctos). 8 records from naturgucker. 130 records from CAS Mammalogy (MAM). 454 records from UMMZ Mammal Collection. 7 records from Tissues Specimens. 120 records from SBMNH Vertebrate Zoology. 5 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 290 records from LACM Vertebrate Collection. 21 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 124 records from Mamíferos de Nuevo León, México (UANL). 78 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 3 records from Macaulay Library Audio and Video Collection. 288 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 2 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 75 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 1: Estado de México, Hidalgo, San Luis Potosí y Tlaxcala. 17 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 7 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mamíferos. 134 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 17 records from Computarización de la Colección Regional Durango (Mammalia). 46 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 44 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 6 records from Mastofauna de la vertiente occidental (oeste) del Parque Nacional Pico de Orizaba, Puebla (Fase 1). 28 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 20 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 4 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 8 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 2 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 62 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2. 1 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 4 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 124 records from Los mamíferos del estado de Durango, México. 30 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 7 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 120 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 6 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 4 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 5 records from Incorporación de nuevos registros de mamíferos de la región Sierra Norte de Oaxaca. 43 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1952 records from Actualización de la base de datos del Atlas Mastozoológico de México. 1 records from ISU Mammals. 10 records from NMNH Extant Specimen and Observation Records. 26 records from UWBM Mammalogy Collection. 21 records from UF Florida Museum of Natural History Mammals. 2 records from NYSM Mammals. 529 records from LSUMZ Mammals Collection. 445 records from Paleobiology Database. 176 records from Mammals Specimens. 19 records from FHSM Mammals Collection. 603 records from CNMA/Colección Nacional de mamíferos. 16 records from Mammal specimens. 33 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 866 records from TTU Mammals Collection. 78 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 124 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1 records from WNMU Mammal Collection (Arctos). 31 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 12 records from PSM Vertebrates Collection. 345 records from UAZ Mammals. 7 records from CNMA/Colección de Mamíferos de la Estación de Biología Los Tuxtlas. 1 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 941 records from MSB Mammal Collection (Arctos). 169 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 2 records from UTEP Vertebrates. 217 records from UTEP Mammals (Arctos). 24 records from Mammalogy Collection - Royal Ontario Museum. 1 records from Anymals+plants - Citizen Science Data. 22 records from NCSM Mammals Collection. 8 records from TTRS Mammals. 3 records from UWYMV Mammal Collection (Arctos). 319 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences